1994
DOI: 10.1111/j.1748-1716.1994.tb09766.x
|View full text |Cite
|
Sign up to set email alerts
|

Cooling effects on the histaminergic response of rabbit ear and femoral arteries: role of the endothelium

Abstract: The effects of cooling on the isometric response of rabbit isolated central ear (cutaneous) and femoral (non-cutaneous) arteries to histamine were determined at 37 degrees C and 24 degrees C (cooling). Under resting tension, both types of arteries contracted to histamine (10(-7)-10(-3) M), and the sensitivity of ear arteries, but not of femoral arteries was lower at 24 than at 37 degrees C. Chlorpheniramine (10(-7) M) blocked the contraction of both types of arteries to histamine at both temperatures. In ear a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 21 publications
4
21
2
Order By: Relevance
“…However, Monge et al (25) reported that changes in temperature might affect the production of NO in a different way depending on vascular beds. Moreover, it is also reported that the increased sensitivity of the relaxation in ear arteries (cutaneous vessels), but not in femoral arteries (deep vessels), to histamine found during cooling seems to be independent of the release of NO (24). The discrepancy between this study (24) and ours may be related to the different relaxant agent used.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…However, Monge et al (25) reported that changes in temperature might affect the production of NO in a different way depending on vascular beds. Moreover, it is also reported that the increased sensitivity of the relaxation in ear arteries (cutaneous vessels), but not in femoral arteries (deep vessels), to histamine found during cooling seems to be independent of the release of NO (24). The discrepancy between this study (24) and ours may be related to the different relaxant agent used.…”
Section: Discussioncontrasting
confidence: 62%
“…On the other hand, there are limited and confl icting reports about the effects of cooling due to using vasodilator agents and tissues. For example, Fernandez et al (24) reported that cooling increased the sensitivity of the relaxation of the central ear artery, a cutaneous vessel, but it did not affect the response of the femoral artery, a noncutaneous vessel, to histamine. It has also been shown that the relaxation to cholinergic stimulation of ear artery, but not of femoral artery, from rabbit was increased during cooling (25).…”
Section: Discussionmentioning
confidence: 99%
“…15) On the other hand, there are limited and con‰icting reports about the eŠects of cooling due to using vasodilator agents and tissues. For example, Fernandez et al 27) reported that cooling increased the sensitivity of the relaxation of the central ear artery, a cutaneous vessel, but it did not aŠect the response of the femoral artery, a noncutaneous vessel, to histamine. It has also been shown that the relaxation to cholinergic stimulation of ear artery, but not of femoral artery, from rabbit was increased during cooling.…”
Section: Discussionmentioning
confidence: 99%
“…It is also reported that the increased sensitivity of the relaxation in ear arteries, but not in femoral arteries, to histamine found during cooling seems to be independent of the release of nitric oxide. 27) Recent studies in humans have shown that the sustained vasoconstrictor responses during local skin cooling is reduced by an nitric oxide synthase inhibitor, suggesting the involvement of nitric oxide synthase inhibition by cooling in the response. 32,33) However, no studies have analyzed the role of nitric oxide on diazoxide, isoproterenol and magnesium sulphate induced relaxation during cooling of human umbilical artery.…”
Section: Discussionmentioning
confidence: 99%
“…For example, nitric oxide is quickly oxidized to form nitrite. To confi rm the involvement of endothelium-dependent mechanisms on hypothermia-induced vasorelaxation, Fernández et al (23) demonstrated that exposure of rabbit ears and femoral arteries to hypothermia (24 °C) increased nitrite production, an indirect indicator of nitric oxide production. In contrast, Chung et al (21) demonstrated by radioimmunoassay that cGMP is enhanced in the endothelium-intact rings at 25 °C, suggesting that moderate hypothermia stimulates the release of endothelial nitric oxide, which activates the GC-cGMP pathway in vascular smooth muscle cells and consequently relaxes vascular tone.…”
Section: Discussionmentioning
confidence: 99%